HUBUNGAN ANTARA SUASANA (CLIMATE) BELAJAR DENGAN SIKAP PENOLAKAN BOLOS SEKOLAH DARI SISWA SMP NEGERI 15 MEDAN - R.L. Holmes Parhusip (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to examine the truth of the relationship between the atmosphere of learning and the attitude of refusal to skip student school. This research was conducted at the 15 Medan State Middle School in the academic year 2017/2018. The population in this study were all second grade students of Medan State Middle School totaling 360 people. The sampling technique used in this study is random sampling. The sample of this study is 90 people, namely 25% of the population. From the results of the analysis carried out conclusions the level of tendency of the Learning Atmosphere in SMP Negeri 15 Medan is still lacking and sufficient. The tendency for the attitude of rejecting school absenteeism from second grade students of SMP Negeri 15 Medan is quite high. There is a relationship that is positively and significantly directly proportional between the learning atmosphere and the attitude of refusal to skipping school actions from the second grade students of SMP Negeri 15 Medan.Keywords: Climate, Relationships, Learning, Cakes Attitude